2022
DOI: 10.1088/1755-1315/983/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of epidemic situation on total electricity consumption of the United States under the prediction scenario

Abstract: The outbreak of COVID-19 epidemic has led to a decline in electricity consumption in the United States, the world’s second largest consumer of electricity. Based on the monthly data of the United States from August 2015 to July 2020, this paper uses the ARIMA model and the ARIMA-BP model to forecast the power consumption of the United States in the next 17 months. The Mean Absolute Percentage Error (MAPE) is 5.6% and 4.5% respectively. It shows that the prediction results have high reliability. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…They also show that COVID-19 adversely affects the prediction accuracy of the ARIMA model. Ma and Wang (2022) combined an ARIMA model with a backpropagation artificial neural network (BP) ML model to predict electricity consumption in the US, demonstrating that the combined model (ARIMA-BP) outperformed the ARIMA model. The results also showed that the COVID-19 pandemic decreased energy consumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also show that COVID-19 adversely affects the prediction accuracy of the ARIMA model. Ma and Wang (2022) combined an ARIMA model with a backpropagation artificial neural network (BP) ML model to predict electricity consumption in the US, demonstrating that the combined model (ARIMA-BP) outperformed the ARIMA model. The results also showed that the COVID-19 pandemic decreased energy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The first class of models, the traditional econometric models has, up to recently, dominated the empirical applications with a more focus in using linear time series models such as ARMA, ARIMA, SARIMA, VAR model, etc... Atalay, Calis, Kus, and Kuru (2019), Cihan (2022), Ensafi, Amin, Zhang, and Shah (2022), Lehna, Scheller, and Herwartz (2022) and Ma and Wang (2022). The use of this class of models is mainly motivated by the simplicity and the ease of estimation of these models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation